Transformasi Pendidikan dalam Pemikiran Abuddin Nata: Pendekatan Filosofis dan Praktis untuk Peningkatan Mutu - Azwanda, Yuri El Hanif; Attoillah, Muhammad Farhan; Roza, Ellya (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
This article examines Abuddin Nata's thoughts on educational transformation, focusing on philosophical and practical approaches that can improve the quality of education in Indonesia. Abuddin Nata's ideas emphasize the importance of holistic education, which not only develops intellectual aspects but also integrates spiritual and moral values to shape balanced individuals. Through a qualitative approach and literature study, this article discusses key concepts in Abuddin Nata's thought, such as the integration of Islamic values into the curriculum, the role of teachers as agents of change, and the significance of character-based education. The findings show that Abuddin Nata's ideas are relevant in addressing current educational challenges, providing direction for improving the quality of education that focuses not only on academic achievement but also on character and moral development of learners. Thus, the educational transformation in Abuddin Nata's thought offers solutions to create more meaningful and relevant education to meet the needs of the times.